Profesionalisme Aparatur Negara: Studi Kasus Pada Tata Kelola Kepagawaian FISIP Universitas Jember - Buntari, Buntari (Journal of Social and Political Science, 2017)
This study focuses on governance kepegawiaan based on the principle of professionalism of the state apparatus. Taking the example of a case on staffing performance FISIP, investigators found an organizational culture that is formed not only on the formal character but touches on the level of informal and personal character. At this point the researchers noticed that the issue of performance, an intersubjective relationship. The study used a qualitative approach with emphasis on descriptions of social relations. With this research, that need to be recommended is; improvement of individual initiatives, to strengthen the sense of identity of employees as part of the Faculty of Social UNEJ and not identity between groups or class, improve the system of rewards, conflict management and improve communication both top down and bottomup. Budaya organization, not just look at how the individuals position became indivisibility with his work, but to see how the work and social relations in the workplace, can strengthen social ties. Social bond is then able to be a crucial point that can be used as a booster of social solidarity.